Children with Disabilities in Canada during the COVID-19 Pandemic: An Analysis of COVID-19 Policies through a Disability Rights Lens - Keiko Shikako; Raphael Lencucha; Matthew Hunt; Sébastien Jodoin-Pilon; Ananya Chandra; Anna Katalifos; Miriam Gonzalez; Sakiko Yamaguchi; Roberta Cardoso; Mayada Elsabbagh; Anne Hudon; Rachel Martens; et al. (MDPI AG, 2023)
Children with disabilities were especially vulnerable during the COVID-19 pandemic, and policies designed to mitigate its effects were limited in addressing their needs. We analyzed Canadian policies related to children with disabilities and their families during the COVID-19 pandemic to identify the extent to which these policies aligned with the United Nations Convention on the Rights of Persons with Disabilities (UN CRPD) and responded to their mental health needs by conducting a systematic collection of Canadian provincial/territorial policies produced during the pandemic, building a categorization dictionary based on the UN CRPD, using text mining, and thematic analysis to identify policies' alignment with the UN CRPD and mental health supports. Mental health was addressed as a factor of importance in many policy documents, but specific interventions to promote or treat mental health were scarce. Most public health policies and recommendations are related to educational settings, demonstrating how public health for children with disabilities relies on education and community that may be out of the healthcare system and unavailable during extended periods of the pandemic. Policies often acknowledged the challenges faced by children with disabilities and their families but offered few mitigation strategies with limited considerations for human rights protection.